Pkd2 Affects Cilia Length and Impacts LR Flow Dynamics and Dand5 - Jacinto, Raquel; Sampaio, Pedro; Roxo-Rosa, Mónica; Pestana, Sara; Lopes, Susana S. (Frontiers in Cell and Developmental Biology, 2021)
The left-right (LR) field recognizes the importance of the mechanism involving the calcium permeable channel Polycystin-2. However, whether the early LR symmetry breaking mechanism is exclusively via Polycystin-2 has not been tested. For that purpose, we need to be able to isolate the effects of decreasing the levels of Pkd2 protein from any eventual effects on flow dynamics. Here we demonstrate that curly-up (cup) homozygous mutants have abnormal flow dynamics. In addition, we performed one cell stage Pkd2 knockdowns and LR organizer specific Pkd2 knockdowns and observed that both techniques resulted in shorter cilia length and abnormal flow dynamics. We conclude that Pkd2 reduction leads to LR defects that cannot be assigned exclusively to its putative role in mediating mechanosensation because indirectly, by modifying cell shape or decreasing cilia length, Pkd2 deficit affects LR flow dynamics.